PROGRAM INFORMATION A CCORDING TO THE FOUR SCHOOLS OF RAMADAN FASTING USING VISUAL BASIC 6.0 - Ahmad Bahrudin; Ire Puspa Wardhani, SKom, MM (Jurnal Sistem Informasi, 2002)
In the Islamic religion has known the existence of four school as fundamental in conducting worship, one of whom worship the fast of Ramadan. Many who thought that the exercise of worship will be contradictory and conflicting objectives and the similarity between the four fasting nature itself. This program is designed to provide information about the Five Pillars, Terms, and the things that broke the fast by the fourth such school. The use of Visual Basic 6.0 is meant to display generated can be used easily by users of various circles of this program.